2015
DOI: 10.3892/etm.2015.2857
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical value of 18F-FDG PET/CT in hepatic alveolar echinococcosis before and after autologous liver transplantation

Abstract: The aim of this study was to evaluate the clinical value of 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in advanced liver alveolar echinococcosis (LAE) prior to and following autologous liver transplantation (ALT). The biodistribution of lesions in 8 patients was recorded using 18F-FDG PET/CT prior to and following surgery. The maximum standardized uptake value (SUVmax) of the lesions was also measured and compared with the pathological results. The overall hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The treatment of the advanced HAE, especially the necessity of aggressive operations, is disputed. [15][16][17] In the retrospective study, we analyzed 42 patients with advanced HAE treated with palliative resection, palliative nonresective procedures, OLT, or albendazole therapy alone. These patients were not randomized and that treatments were based on disease presentations, individual wishes, and physician choices as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of the advanced HAE, especially the necessity of aggressive operations, is disputed. [15][16][17] In the retrospective study, we analyzed 42 patients with advanced HAE treated with palliative resection, palliative nonresective procedures, OLT, or albendazole therapy alone. These patients were not randomized and that treatments were based on disease presentations, individual wishes, and physician choices as well.…”
Section: Discussionmentioning
confidence: 99%
“…The management of advanced HAE, especially the necessity of aggressive operations, like palliative resection and orthotopic liver transplantation (OLT), remains controversial. [15][16][17] …”
Section: Introductionmentioning
confidence: 99%
“…18 F-FDG PET/CT demonstrates metabolic activity and so can effectively determine the biological boundary of liver AE along with the metabolic activity of surviving liver following autologous liver transplantation [77] and is, therefore, recommended for the initial assessment and follow-up of human AE [78]. In a recent study, CEUS and 18 F-FDG PET showed good inter-rater reliability in determining the activity of hepatic AE [60].…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…Then, the CT data were applied to perform attenuation corrections for the PET images. The ordered subset expectation maximization iterative method was used to reconstruct the images of the cross-sectional, coronal and sagittal planes, as well as the PET/CT fusion images [10].…”
Section: F-fdg-pet/ct and Tbrsmentioning
confidence: 99%